A system dynamics approach to logistics outsourcing policies and decisions - Raul Arellano Caldeira Franco; Hugo Tsugunobu Yoshida Yoshizaki; José Geraldo Vidal Vieira (Production)
Abstract This paper is based on a revelatory single-case study that uses a system dynamics model to analyze the costs and policies of a distribution logistics outsourcing process (i.e., the warehousing and transportation activities) of a Brazilian consumer packaged goods (CPG) company. The model considers the costs before and after the outsourced operation startup and how these costs influence the net present value (NPV) of the process. The model’s findings suggest policies, such as the reduction of the ex-ante period and the ex-ante reactive and proactive monitoring of operations, to obtain optimal financial results. In addition, the model provides guidelines for the contract lengths and demonstrates that in the outsourcing process, the greatest gains result during periods of low inflation and low interest rates in a stable economy.